Effect of Fetal Growth on 1‐Year Mortality in Neonates With Critical Congenital Heart Disease. Issue 17 (4th September 2018) - Steurer, Martina A.; Baer, Rebecca J.; Burke, Edmund; Peyvandi, Shabnam; Oltman, Scott; Chambers, Christina D.; Norton, Mary E.; Rand, Larry; Rajagopal, Satish; Ryckman, Kelli K.; Feuer, Sky K.; Liang, Liang; et al.
Abstract : Background: Infants with critical congenital heart disease (CCHD) are more likely to be small for gestational age (GA). It is unclear how this affects mortality. The authors investigated the effect of birth weight Z score on 1‐year mortality separately in preterm (GA <37 weeks), early‐term (GA 37–38 weeks), and full‐term (GA 39–42 weeks) infants with CCHD. Methods and Results: Live‐born infants with CCHD and GA 22 to 42 weeks born in California 2007–2012 were included in the analysis. The primary predictor was Z score for birth weight and the primary outcome was 1‐year mortality. Multivariable logistic regression was used. Results are presented as adjusted odds ratios and 95% confidence intervals (CIs). The authors identified 6903 infants with CCHD. For preterm and full‐term infants, only a Z score for birth weight <−2 was associated with increased mortality compared with the reference group ( Z score 0–0.5, adjusted odds ratio, 2.15 [95% CI, 1.1–4.21] and adjusted odds ratio, 3.93 [95% CI, 2.32–6.68], respectively). In contrast, in early‐term infants, the adjusted odds ratios for Z scores <−2, −2 to −1, and −1 to −0.5 were 3.42 (95% CI, 1.93–6.04), 1.78 (95% CI, 1.12–2.83), and 2.03 (95% CI, 1.27–3.23), respectively, versus the reference group. Conclusions: GA seems to modify the effect of birth weight Z score on mortality in infants with CCHD. In preterm and full‐term infants, only the most severe small‐for‐GA infants ( Z score <−2) were at increased risk for mortality, while, in early‐term infants, the risk extended to mild to moderate small‐for‐GA infants ( Z score <−0.5). This information helps to identify high‐risk infants and is useful for surgical planning.